Альберт Лорд як епічний співець - Віллс, Д. (Народна творчість та етнологія, 2012)
Jeffrey Wills. Albert Lord as a Singer of Tales. Although Albert Lord was well-versed in dispassionate scholarly prose, he had also been a field worker and collector of epics, who was acutely aware of his role in the audience. Like other modern anthrophologist, he knew that the observer is also always being observed. And so here I want to observe Albert Lord as a scholar. Не is also our tale singster.